The Effect of E-Performance and Work Environment on Employee Performance Through Work Discipline of The General Bureau of The Regional Secretariat of North Sulawesi Provincial Office - Kaunang, Michelle M.K.; Sendow, Greis M.; Pandowo, Merinda H. Ch. (Abdurrauf Science and Society, 2025)
This study aims to analyze the influence of E-Performance and work environment on employee performance, with work discipline as an intervening variable at the General Bureau of the Regional Secretariat of North Sulawesi Province. The problems raised are related to the stagnation of employee performance even though the E-Performance system has been implemented and the work environment has been improved. This study uses a quantitative approach with a survey method through a questionnaire to 81 ASN employees and is analyzed using Structural Equation Modeling with SmartPLS 3.0. The results of the study indicate that E-Performance has a positive and significant effect on work discipline and employee performance. The work environment has a significant effect on work discipline, but does not have a direct effect on employee performance. Work discipline is proven to have a significant effect on employee performance, as well as mediating the relationship between E-Performance and the work environment on employee performance. This finding confirms that improving employee performance requires the support of an effective digital system and a comfortable work environment, accompanied by strong disciplinary coaching.